Are you really my clone? Identity verification of the in-trust sweetpotato collection at the International Potato Center. - Ellis, David; Barkley, N.A.; Rossel, G.; Khan, A.; Kilian, Andrzej (PAG, 2016)
The global in-trust sweetpotato collection maintained by the International Potato Center (CIP) in Lima, Peru consists of over 5,000 cultivated sweetpotato accessions maintained as clones in vitro as well as over 1,000 accessions from 67 species of Ipomoea maintained as seed populations. The clonal sweetpotato collection at CIP was initiated in the 1980’s and for 60% of the collection, original material still exists as potted plants in the greenhouse. This provides a unique opportunity where genetic integrity of a clonal collection, maintained in vitro for the past thirty years, can be confirmed by a side-by-side comparison of the same accession from the greenhouse. Initial molecular comparison is done using a set of twenty SSR primers followed by side-by-side comparison in the field using 30 morphological descriptors. Confirmation of identity requires both genetic and morphological analysis as a low percentage of the accessions appear to be duplicates based on SSR yet are morphologically distinct. Historical morphological descriptor data is used as a check to confirm identity and is being used as the sole check for accessions where we do not have original material for comparison. SSR results from 70% of the collection has confirmed that 85% of the in vitro accessions are true-to-type. In vitro accessions which are not true-to-type are reisolated and cleaned of viruses from the confirmed true-to-type greenhouse accessions. Accessions which are true-to-type are fingerprinted using DArTseq to provide a sequence-based fingerprint.